2020
DOI: 10.1016/j.cub.2020.03.057
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of homozygous knock-out sea urchins

Abstract: know of no comparative cross-cultural research on vocal rates of infant boys and girls nor on possible differences in caregiver speech to boys and girls across cultures. A non-signifi cant tendency for caregivers to speak more to boys was seen in our data (see Supplemental Results), and other possible cultural factors could also infl uence sex differences in infant vocal rates (see Supplemental Discussion).It is possible that the sex difference is not closely related to language capability -the CBR did not sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 8 publications
1
32
0
Order By: Relevance
“…From an intense red sea star ( Fromia milleporella ) to a black and white striped brittle star ( Ophiactis savignyi ) to the variegated sea urchin ( Lytechinus variegatus), pigment is a pervasive feature of this phylum. Because of the molecular techniques now available for echinoderms, mechanisms controlling pigmentation in these animals are being revealed ( Hira et al, 2020 ; Liu et al, 2019 ; Wessel et al, 2020 ; Yaguchi et al, 2020 ). The purple sea urchin, Strongylocentrotus purpuratus , provides a molecularly tractable model organism to dissect the developmental importance of pigmented cells, and the biosynthesis of their pigment.…”
Section: Introductionmentioning
confidence: 99%
“…From an intense red sea star ( Fromia milleporella ) to a black and white striped brittle star ( Ophiactis savignyi ) to the variegated sea urchin ( Lytechinus variegatus), pigment is a pervasive feature of this phylum. Because of the molecular techniques now available for echinoderms, mechanisms controlling pigmentation in these animals are being revealed ( Hira et al, 2020 ; Liu et al, 2019 ; Wessel et al, 2020 ; Yaguchi et al, 2020 ). The purple sea urchin, Strongylocentrotus purpuratus , provides a molecularly tractable model organism to dissect the developmental importance of pigmented cells, and the biosynthesis of their pigment.…”
Section: Introductionmentioning
confidence: 99%
“…(a) Mutation efficiency with Smad2/3 sgRNA and Cas9 mRNA injection. The length of PCR fragment for the wild type Smad2/3 is designed as 331 bp, and a mixture of 174 bp and 157 bp cleaved bands by CRISPR/Cas9 system were detected in mutant individuals (method for mutation analysis is in (Yaguchi et al., 2020)). The numbering ladder of the left side of the image shows the size marker of DNA fragment.…”
Section: Establishment Of Homozygous Knockout Sea Urchins Resulted In Completely Albino Strainsmentioning
confidence: 99%
“…Next, we tried to edit a nonlethal gene: the pigment‐related gene polyketide synthase 1 ( Pks1 ) as previously published (Yaguchi et al., 2020). The knockdown and F0 knockout phenotypes for this gene have already been reported, and the results indicated that sea urchins can survive and remain healthy without Pks1 function (Liu et al., 2019; Oulhen & Wessel, 2016).…”
Section: Establishment Of Homozygous Knockout Sea Urchins Resulted In Completely Albino Strainsmentioning
confidence: 99%
“…However, CRISPR/Cas9-mediated editing has highly variable efficiency in the F 0 generation, dependent on numerous factors including: the choice of physical delivery method, molecular delivery of CRISPR components, sgRNA length and sequence, cell type and organism (Zhang et al, 2016;Lino et al, 2018). In sea urchins, this technique has only been used in a handful of studies to date (Lin and Su, 2016;Shevidi et al, 2017;Liu et al, 2019;Wessel et al, 2020;Yaguchi et al, 2020), all of which have targeted genes in which a mutation confers an easily visualized, and previously established, phenotype.…”
Section: Discussionmentioning
confidence: 99%